A Matter of Extreme Indelicacy: Neo-Victorian Critical Memory in Kind Hearts and Coronets (1949) - Eduardo Valls Oyarzun (Current Swedish Archaeology, 2022)
Critical assessments of Robert Hamer’s Kind Hearts and Coronets (1949) more often than not aim solely at discussing a larger cultural phenomenon, to wit, the Ealing Comedies and their impact on post-war Britain. Readings outside this paradigm are scarce. The film, however, engages with several issues the recent phenomena of neo-Victorian fiction and film consistently address. These are the relationship between the past and the present (as well as the capital role memory plays in it), nostalgia as the underlining desire for the new recasting of Victoriana, the reassessment of history through marginal and/or alternative identities, as well as the blatantly post-modern continuous deferral of meaning. This article explores these issues in order to inscribe the film within neo-Victorian aesthetics, not only to update the critical discourse about the film, but also to reveal what the film has to say about neo-Victorian culture.